Fooding Pattern on Stunting Toddlers - Ni Putu Aryani; Baiq Ricca Afrida; Susilia Idyawati; Nurul Hikmah Annisa (Jurnal Keperawatan, 2022)
High rate of stunting in Lombok, especially West Lombok can give an impact on health, especially the mothers and their babies. Based on several research results, one factors that causing of high rate of stunting was food pattern. The aim of this research was to determine the barriers of parenting on mothers who have stunting toddlers. Research method used in this research was qualitative using in-depth interviews. The sampling technique used in this research was non-probability sampling with purposive method. The numbers of samples in this research were 8 mothers who have stunting toddlers. Data analysis was carried out with processing transcripts of interview results by providing code (coding) to words or sentences to facilitate the analysis of information obtained from one informant to another. The result of data analysis was presented using narration or descriptions according to the patterns found. The result of the research that have been carried out showed that the eating pattern on stunting toddlers was situational where parents do not apply certain parenting patterns but they were adapted to certain conditions and situations, especially on diet menu, meal schedule, meal portions, and the attitude of the mother when their kids don't want to eat.